THE RECONSTRUCTION OF INDONESIAN SHIPPING LAW IN THE SEA TRANSPORTATION SYSTEM FOR A SUCCESSFUL SEA TOLL PROGRAM AND IMPROVEMENT OF SHIPPING ADMINISTRATION - Victoria, Ong Argo; Pambudi, M. Aji Luhur; Dewi, Ratna K. (UNISSULA, 2022)
Indonesia uses Pancasila Democracy as the main foundation as well as a source of law in the nation and state (staatfundamentalnorm). One of the sounds of the 5th principle of Pancasila is,